Associations between Parity, Hair Hormone Profiles during Pregnancy and Lactation, and Infant Development in Rhesus Monkeys (Macaca mulatta). - Amanda M Dettmer; Kendra L Rosenberg; Stephen J Suomi; Jerrold S Meyer; Melinda A Novak (PLoS ONE)
Studies examining hormones throughout pregnancy and lactation in women have been limited to single, or a few repeated, short-term measures of endocrine activity. Furthermore, potential differences in chronic hormonal changes across pregnancy/lactation between first-time and experienced mothers are not well understood, especially as they relate to infant development. Hormone concentrations in hair provide long-term assessments of hormone production, and studying these measures in non-human primates allows for repeated sampling under controlled conditions that are difficult to achieve in humans. We studied hormonal profiles in the hair of 26 female rhesus monkeys (Macaca mulatta, n=12 primiparous), to determine the influences of parity on chronic levels of cortisol (hair cortisol concentration, HCC) and progesterone (hair progesterone concentration, HPC) during early- to mid-pregnancy (PREG1), in late pregnancy/early lactation (PREG2/LACT1), and in peak lactation (LACT2). We also assessed infants' neurobehavioral development across the first month of life. After controlling for age and stage of pregnancy at the first hair sampling period, we found that HCCs overall peaked in PREG2/LACT1 (p=0.02), but only in primiparous monkeys (p<0.001). HPCs declined across pregnancy and lactation for all monkeys (p<0.01), and primiparous monkeys had higher HPCs overall than multiparous monkeys (p=0.02). Infants of primiparous mothers had lower sensorimotor reflex scores (p=0.02) and tended to be more irritable (p=0.05) and less consolable (p=0.08) in the first month of life. Moreover, across all subjects, HCCs in PREG2/LACT1 were positively correlated with irritability (r(s)=0.43, p=0.03) and negatively correlated with sensorimotor scores (r(s)=-0.41, p=0.04). Together, the present results indicate that primiparity influences both chronic maternal hormonal profiles and infant development. These effects may, in part, reflect differential reproductive and maternal effort in mothers with varied caretaking experience. In addition, infant exposure to relatively higher levels of maternal cortisol during the late fetal and early postnatal periods is predictive of poorer developmental outcomes.